The Immunological Effect of a Gleevec Drug as Tyrosin Kinase Inhibitor in Auto-immune Thyroid Peroxidase in Iraqi Patientswith Chronic Myeloid Leukemia - Muhammed, Haidar; Ali, Ekhlass; Yaseen, Yusra (Iraqi Journal of Science, 2025)
A gleevec drug a tyrosine kinase inhibitor that targets the so-called Philadelphia chromosome that characteristic of chronic myeloid leukemia (CML) which has been widely used in treatment of several hematological malignancies, and there is concern about the long-term immune effects of its use. Autoimmune disorders in patients treated with gleevec drug may be related to the direct immune modulating properties or may be linked to a possible toxic effect in target organs, triggering autoimmunity diseases. The study described the development of symptomatic autoimmune thyroid peroxidase antibodies (TPO) in 51 patients with CML compared with 10 subjects as healthy control. The samples collected from Iraqi National Center for Research and Treatment of Hematological Diseases/University of Al-Mustansiryiah.Epidemiological data such as age, sex and cure period were recorded for all of the patients. The range age of the patients were (16-70) years male and female with a cure period (8 months to 10 years) in chronic treatment with recombinant a gleevec drug. The samples tested for anti-TPO by using Enzyme Linked Immune Sorbent Assay (ELISA) which revealed significant differences (p<0.05) between control and patients. The patient’s samples diagnosed for chronic myelogenous leukemia according to clinical physical examinations, Real-time polymerase chain reaction (RT-PCR) for detection quantification of mRNA chimerical gene bcr/abl (M-bcr) and mRNA gene/abl and by Fluorescence in Situ Hybridization (FISH) techniques in the clinical material. The aim of the study was to test the possible association of the generation of autoimmune disease on thyroid peroxidase by the effect of gleevec drug in patients with CML